Perancanagan Sistem Informasi Perpustakaan dengan Internet of Things (IoT) Menggunakan Perangkat Radio Frekwensi Identification Berbasis Nodel Mcu Pada SMKN - UC Mariance; Irwan; Muhammad Arief; Salman Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research is a software research and development (software research and development) which aims to find out the results of the development of the Internet Of Thinking at SMK Negeri 9 Medan. Data was collected using interviews, questionnaires, measurements and documentation. Data were analyzed using descriptive statistical analysis techniques. The results of the research produce an e-library application that is used in library processing by utilizing the Internet of Think (IOT). The test results show very good results based on 5 aspects of ISO 25010 characteristics, namely: functional suitability in the good category, usability with the test results in the very decent category, portability with the test results running well on nine different types of Android, performance efficiency with good test results, and compatibility with test results can run well when run concurrently with other applications.